George Dana Boardman papers - Boardman, George Dana, 1828-1903.
Volume containing letters to Boardman from college presidents and others relating to his proposal to establish a national Christian university in Washington, D.C.
Baptist clergyman.
Collection material in English.
Keywords: Baptists -- Clergy; Christian universities and colleges -- Washington (D.C.); Universities and colleges -- Washington (D.C.); Clergy